(untitled) (Salam International Academic Journal, 2023)
This scholarly research delves into the multifaceted narratives surrounding the period of revelation interruption and the profound emotional state experienced by the revered Prophet Muhammad (peace be upon him). While authentic narrations discuss the initial revelation of the Holy Qur’an and its subsequent interruption for a brief period, certain unverified and unreliable narrations not only describe revelations occurring during sleep but also implicate the Prophet (PBUH) in contemplating suicide. The compilation of Hadiths by Al-Bukhari consistently emphasizes wakeful revelations and does not allude to the Prophet’s suicidal intentions. However, a singular narration attributed to Ma’mar bin Rashid San’ani, transmitted from Imam Ibn Shihab Zuhri, introduces the notion of the Prophet’s contemplation of suicide following the interruption of revelation. Curiously, Imam Ibn Shihab Zuhri conveys this narration without providing a specific chain of narrators, employing the phrase “«فیما بَلَغَنَا»” (as it has reached us). It is essential to recognize that Imam Zuhri occupied a subordinate position among the Tabi’in (successors to the Companions of the Prophet), and a considerable temporal gap separated him from the Prophet (PBUH). Consequently, eminent Hadith scholars criticized Zuhri’s Marasil (reports transmitted without a complete chain of narrators) as weak and unreliable. Furthermore, other Hadiths corroborating this unfounded narrative, as found in works by Tabari and Tabaqat Ibn Sa’d, exhibit textual deficiencies and inconsistencies with authentic narrations and rational reasoning.